مركزية الأخلاق في الفكر المقاصدي عند العز بن عبدالسلام: دراسة دعوة الأخلاق التحسينية - بكور، بشار محمد (الجامعة الإسلامية العالمية, 2022)
البعثة النبوية ذات رسالة أخلاقية، وإنما جاءت الشريعة الإسلامية لتحقيق مصالح العباد في الدنيا والآخرة، وعلى الرغم من وثاقة الصلة بين الأخلاق والمصالح؛ اعتاد جمهور علماء الأصول - قديما وحديثا - وضع مكارم الأخلاق في المقاصد التحسينية؛ المرتبة الثالثة في التقسيم الأصولي للمقاصد، مما أثار استشكالا عند بعض الكتاب المعاصرين؛ لما ينطوي عليه هدا التصرف من زحزحة للمكانة السامية التي تمتاز بها القيم الأخلاقية في الشريعة الإسلامية، وعليه؛ يهدف البحث إلى إثبات مركزية البعد الأخلاقي في الشريعة بعامة، وفي علم المقاصد بأقسامه الثلاثة (الضرورية والحاجية والتحسينية) بخاصة؛ عند الإمام الأصولي المجتهد العز بن عبدالسلام الذي قدم منظومة أخلاقية مقاصدية متميزة في كتابه "شجرة المعارف والأحوال وصالح الأقوال والأعمال"، ويمضي البحث في التحليل والمناقشة لمفاهيم أصولية ومنهجية في مقاربة لحل إشكالية "الأخلاق التحسينية" عند الفقهاء والأصوليين الذين ما برحوا يقررون أن الشريعة في مجامعها وأصولها جلب للمكارم والفضائل، ونهي عن الفواحش والرذائل، وحيثما وجدت المصلحة فثم خلق صالح. The prophetic mission has a moral message, hence came the Islamic law to secure the interests of people in this world and the hereafter. Despite the close relationship between morals and interests, most scholars of Islamic jurisprudence - both in the past and in the present - are accustomed to placing good morals within the maqāsid taḥsiniyyah (ameliorative objective of the jurisprudence); at the third place is in the jurisprudic categorisation of the objectives of the Syarīʿah. This categorisation had resulted in some confusion among some contemporary writers since it implies that this a displacement of the lofty position that the moral values occupy in the Syarīʿah. In relation to this, the study aims to prove the centrality of the ethical dimension in the Sharīʿah in general, and in the discipline of Sharīʿah objectives in their three categories (ḍaruruyyah, ḥājiyyah, taḥsiniyyah) in particular from the view of the jurisprudence scholar Imam Al-ʿIzz bin ʿAbd al-Salām, who composed an outstanding ethical system according to the framework of the objectives of the Sharīʿah in his book entitled “The Tree of Knowledge, Conditions and Commendable Sayings and Actions.” (Syajarat al-Maʿārif wa al al-Aḥwāl, wa Ṣālih al-Aqwāl wa al-Aʿmāl). The study elaborates on the jurisprudic and methodologocal concepts of ameliorative morals to solve their issues as viewed by the Islamic jurisprudence scholars who continously argue that Sharīʿah is meant predominantly to bring dignity and virtues in addition to uproot evil and vice. Hence, where there is an interest that need to be defended and promoted, there is always a virtue that is intended from it.
Keywords: أصول الفقه الإسلامي -- التشريع الإسلامي -- مكارم الأخلاق -- ابن عبدالسلام، عبدالعزيز بن عبدالسلام بن أبي القاسم، ت. 660 هـ